Konsep Ketuhanan Hindu Dalam Kitab Īśā Upaniṣad: Tinjauan Ontologis Aristoteles - Joyo, Puspo Renan (Fakultas Dharma Duta, 2021)
Associated with the concept of God in Hinduism, in general perspective is still attached to the image of Hinduism as polytheism or a religion that worships many gods. Interestingly, in Īśā Upaniṣad and other Vedic books it shows the opposite, the concept of God in Hinduism is not polytheistic. This article aims to examine the concept of God in Hinduism in the Īśā Upaniṣad book from the perspective of Aristotle’s ontology. This study is a library research using a qualitative approach. The material object of this study is the concept of God in Hinduism in the Īśā Upaniṣad book. The data collection in this study was carried out through document studies on primary and secondary data sources. The data analysis in this study used descriptive, interpretative, and holistic methodical steps. The results of this study show that the concept of God in Hinduism in Īśā Upaniṣad book is monistic. Aristotle's ontological perspective used to portray the concept of god in the Īśā Upaniṣad book can be described in several categories, namely; in substance, quantity, quality, place, time, position, possession and action.